Promoting mixed farming system innovations in Malawi: A unified approach - Mzumara, Edward; Homann-Kee Tui, Sabine; Liben, Feyera; Banda, Mcloyd; Botoman, Lester; Kinyua, Michael; Kihara, Job (CGIAR System Organization, 2024)
“We are all targeting the same farmer,” noted Mr. Raphael Msyali, Chief Agriculture Officer for Mzimba District. Meanwhile, Mrs. Everlister Chidothi, a representative of Traditional Authority Mlumbe in Zomba District, emphasized the need to reach more farmers. These statements, though seemingly contrasting, highlight a common goal from field days in Mzimba and Zomba: the necessity of a unified, collaborative approach to farming systems. To effectively support farmers, organizations implementing diverse innovations must work together to bundle their complementary products and services, addressing farmers’ specific needs.